2006
DOI: 10.2527/jas.2005-308
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the ileal amino acid and energy digestibilities of corn distillers dried grains with solubles using grower-finisher pigs1,2,3

Abstract: An experiment evaluated the ileal apparent and standardized AA and apparent energy digestibilities in grower-finisher pigs of 5 sources of distillers dried grains with solubles (DDGS) from corn. The 5 DDGS sources were analyzed for AA, GE, NDF, ADF, and color score. Diets were formulated to contain 15% CP from the test DDGS sources (approximately 60% of the diet). A low-protein (5% casein) diet was used to estimate basal endogenous AA losses. The experiment was conducted in 2 replicates of a 6 x 6 Latin Square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
4
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 7 publications
17
61
4
6
Order By: Relevance
“…In growing pigs, inclusion of DDGS in the diet has frequently been associated with reduced performance due to lower digestibility and availability of lysine (Fastinger and Mahan, 2006;Stein et al, 2006;Almeida et al, 2011). This was not observed in growing rabbits with our balanced amino acid diets, perhaps due to the digestive particularities of rabbit.…”
Section: Resultsmentioning
confidence: 72%
“…In growing pigs, inclusion of DDGS in the diet has frequently been associated with reduced performance due to lower digestibility and availability of lysine (Fastinger and Mahan, 2006;Stein et al, 2006;Almeida et al, 2011). This was not observed in growing rabbits with our balanced amino acid diets, perhaps due to the digestive particularities of rabbit.…”
Section: Resultsmentioning
confidence: 72%
“…These values are similar to values of 14.43 and 12.71 MJ/ kg of DM in NRC [16], respectively. In some studies [19] it is observed that increasing [5] reported that the energy digestibility has been found to not differ among corn DDGS sources and ranged from 66.7 to 69.2%. However, energy digestibility of DDGS was higher when DDGS was fed in combination with cereal grain instead of cornstarch [11].…”
Section: Results and Discussion Energy Digestibility And Retentionmentioning
confidence: 99%
“…Para suínos, por exemplo, o coeficiente de digestibilidade verdadeira dos DDGS de milho varia entre 43,9 e 63,0% (STEIN et al, 2006). Fastinger & Mahan (2006) Londrina, V. 7, N. 18, Ed. 241, Art.…”
Section: Introductionunclassified
“…241, Art. 1593, Setembro, 2013 A cor do DDGS tem correlação com a digestibilidade de aminoácidos, pois os DDGS com coloração mais escura apresentaram valores menores de digestibilidade (FASTINGER & MAHAN, 2006). Pedersen et al (2005) consideram que os parâmetros de cor, brilho e intensidade do amarelo, são indicadores razoáveis para prever o conteúdo de lisina digestível em DDGS.…”
Section: Introductionunclassified
See 1 more Smart Citation